DigitalVHI--a freeware open-source software application to capture the Voice Handicap Index and other questionnaire data in various languages - Herbst, Christian T; Oh, Jinook; Vydrová, Jitka; Švec, Jan G (Logopedics, phoniatrics, vocology, 2015)
In this short report we introduce DigitalVHI, a free open-source software application for obtaining Voice Handicap Index (VHI) and other questionnaire data, which can be put on a computer in clinics and used in clinical practice. The software can simplify performing clinical studies since it makes the VHI scores directly available for analysis in a digital form. It can be downloaded from http://www.christian-herbst.org/DigitalVHI/.
Keywords: jazyk (prostředek komunikace); Severity of Illness Index; User-Computer Interface; prediktivní hodnota testů; Prognosis; počítačové zpracování signálu; Surveys and Questionnaires; stupeň závažnosti nemoci; Software; počítačová grafika; Voice Disorders; Signal Processing, Computer-Assisted; Computer Graphics; Speech Production Measurement; Language; lidé; Predictive Value of Tests; Disability Evaluation; uživatelské rozhraní počítače; akustika; kvalita hlasu; prognóza; Voice Quality; Voice Handicap Index; měření tvorby řeči; posuzování pracovní neschopnosti; Humans; software application; software; Acoustics; poruchy hlasu; digital; průzkumy a dotazníky; questionnaire